Effect of Near-Fault Earthquake Characteristics on Seismic Response of Mid-Rise Structures with Triple Friction Pendulum Isolator - Ali Majdi; Mohammadreza Mashayekhi; Ataallah Sadeghi-Movahhed (Journal of Rehabilitation in Civil Engineering)
Pulses of near-fault earthquakes are very effective in the seismic response of the Triple Friction Pendulum Isolator (TFPI). In previous studies, the effect of original bi-directional pulses components on the isolated tall buildings by TFPI was neglected. Also, the effect of changing the design parameters of TFPI on preventing seismic disaster in this type of building is unknown. For this reason, a 10 stories moment steel structure mounted on TFPI was designed. Then, the seven pairs of bidirectional near-fault earthquake records without and with removal pulses were applied to the isolated structure. The results show that the seismic responses on the base level decrease by reducing the velocity pulse amplitude (AP) and increasing the velocity pulse period (TP), also if the period of the isolators (TM) is being higher than TP, the seismic responses on the upper floors reduce. Moreover, Increasing the geometrical dimensions of the TFPI can significantly reduce the seismic effect of near-fault earthquake with pulses.